DIGITAL SERVITUDES: A NEW DIMENSION OF LIMITED REAL RIGHTS IN THE DIGITAL ERA - Egamberdiev Eduard Khajibaevich (PT. Antis International Publisher, 2025)
Objective: This study investigates the emerging concept of digital servitudes within the system of limited real rights, exploring its legal nature, relationship with traditional servitudes, and implications in the digital era. Method: Utilizing a comprehensive legal analysis, the research examines legislative frameworks, judicial interpretations, and case studies to elucidate the establishment, implementation, and termination of digital servitudes. Results: The findings reveal that digital servitudes introduce a novel dimension to civil law by extending real rights into virtual spaces, posing unique challenges in protecting participants' rights and resolving digital disputes. The study identifies gaps in current legal systems and suggests mechanisms for safeguarding digital servitude rights. Novelty: This research contributes to legal scholarship by proposing theoretical frameworks and legislative recommendations tailored to the digital environment, specifically aimed at enhancing the legal infrastructure of the Republic of Uzbekistan. The study provides a foundational understanding of digital servitudes, marking a significant advancement in civil law discourse.